Conduction Electrohydrodynamics with Mobile Electrodes: A Novel Actuation System for Untethered Robots. Issue 9 (22nd May 2017) - Cacucciolo, Vito; Shigemune, Hiroki; Cianchetti, Matteo; Laschi, Cecilia; Maeda, Shingo
Abstract : Electrohydrodynamics (EHD) refers to the direct conversion of electrical energy into mechanical energy of a fluid. Through the use of mobile electrodes, this principle is exploited in a novel fashion for designing and testing a millimeter‐scale untethered robot, which is powered harvesting the energy from an external electric field. The robot is designed as an inverted sail‐boat, with the thrust generated on the sail submerged in the liquid. The diffusion constant of the robot is experimentally computed, proving that its movement is not driven by thermal fluctuations, and then its kinematic and dynamic responses are characterized for different applied voltages. The results show the feasibility of using EHD with mobile electrodes for powering untethered robots and provide new evidences for the further development of this actuation system for both mobile robots and compliant actuators in soft robotics. Abstract : Electrohydrodynamics with mobile electrodes is proposed as actuation method for a millimeter‐scale untethered robot, designed as an inverted sail‐boat, with the thrust generated on the sail submerged in the liquid. The results show the feasibility of the approach and provide new evidences for the further development of this actuation system for both mobile robots and compliant actuators in soft robotics.